2022
DOI: 10.1002/advs.202200010
|View full text |Cite
|
Sign up to set email alerts
|

Doping Ruthenium into Metal Matrix for Promoted pH‐Universal Hydrogen Evolution

Abstract: For heterogeneous catalysts, the active sites exposed on the surface have been investigated intensively, yet the effect of the subsurface-underlying atoms is much less scrutinized. Here, a surface-engineering strategy to dope Ru into the subsurface/surface of Co matrix is reported, which alters the electronic structure and lattice strain of the catalyst surface. Using hydrogen evolution (HER) as a model reaction, it is found that the subsurface doping Ru can optimize the hydrogen adsorption energy and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Similarly, as shown in the high-resolution Te 3d XPS profile (Figure c), the two peaks at 575.9 and 586.2 eV could be assigned to Te 4+ , and the other two peaks at 570.0 and 582.3 eV could be attributed to Te 0 . Furthermore, as shown in Figure d, the electron paramagnetic resonance (EPR) profiles revealed a distinct signal at g = 2.003, which is attributed to the oxygen vacancies in Bi/NCNSs and Bi­(Te) 2 /NCNSs. The EPR of Bi­(Te) 2 /NCNSs displayed higher intensity than that of Bi/NCNSs, indicating that Bi­(Te) 2 /NCNSs has more oxygen vacancies due to Te doping. From the above data, it can be inferred that oxidation of the Bi surface was restrained after Te doping, which is beneficial to the formation of the intermediate for formate .…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, as shown in the high-resolution Te 3d XPS profile (Figure c), the two peaks at 575.9 and 586.2 eV could be assigned to Te 4+ , and the other two peaks at 570.0 and 582.3 eV could be attributed to Te 0 . Furthermore, as shown in Figure d, the electron paramagnetic resonance (EPR) profiles revealed a distinct signal at g = 2.003, which is attributed to the oxygen vacancies in Bi/NCNSs and Bi­(Te) 2 /NCNSs. The EPR of Bi­(Te) 2 /NCNSs displayed higher intensity than that of Bi/NCNSs, indicating that Bi­(Te) 2 /NCNSs has more oxygen vacancies due to Te doping. From the above data, it can be inferred that oxidation of the Bi surface was restrained after Te doping, which is beneficial to the formation of the intermediate for formate .…”
Section: Resultsmentioning
confidence: 94%
“…20 The use of noble metal atom doping to adjust the electronic state of the surrounding atoms was also proposed to improve the activity of the catalyst. [34][35][36] Lu et al designed a surface-engineering strategy to dope Ru into the subsurface of the Co matrix as a HER catalyst. 34 DFT results showed that Ru doping in the subsurface dramatically enhances the catalytic activity for the HER and the Ru doped into the subsurface was thermodynamically more stable than that the Ru alloyed on the surface.…”
Section: Strategy For D-band Center Modulationmentioning
confidence: 99%
“…Reproduced with permission. [ 42 ] Copyright 2022, Wiley‐VCH. e) Schematic diagram of the preparative process of CoRu@NG‐x; f) HRTEM image of CoRu@NG‐3.…”
Section: Ph‐universal Ru‐based Electrocatalysts Toward Hermentioning
confidence: 99%